ONE-YEAR RESULTS OF HALF- VERSUS STANDARD-DOSE PHOTODYNAMIC THERAPY COMBINED WITH RANIBIZUMAB FOR POLYPOIDAL CHOROIDAL VASCULOPATHY. Issue 4 (April 2018) - Wong, Ian Y.; Shi, Xuan; Gangwani, Rita; Iu, Lawrence P.; Fung, Nicholas; Li, Qing; Ng, Alex L. K.; Li, Xiaoxin
Abstract : Purpose: To explore the efficacy of half-dose verteporfin photodynamic therapy (hd-PDT) and standard-dose photodynamic therapy (sd-PDT), when combined with ranibizumab in the treatment of polypoidal choroidal vasculopathy. Methods: Subjects were allocated to either the hd-PDT arm or the sd-PDT arm. All subjects received an injection of ranibizumab and PDT treatment (dosage according to allocation) at baseline. Subjects were followed up monthly for 12 months, and re-treatment were given at each visit if criteria were met. Results: There were 26 subjects in the hd-PDT arm and 32 in the sd-PDT arm. Overall mean age was 69.3 ± 9.4 years. Baseline demographics and ocular features did not differ significantly between the two arms. Improvement in vision and reduction in central retinal thickness were similar between the two arms. When presenting, visual acuity was better than 20/50 (logarithm of the minimum angle of resolution 0.4), or when there were three or less polyps angiogram, those treated with hd-PDT tended to perform better than those treated with sd-PDT. Conclusion: In general, hd-PDT was able to produce similar results as sd-PDT. Subgroup analysis revealed superior results with hd-PDT when baseline vision was 20/50 or better, or when there were three or less polyps on indocyanine green angiography. Abstract : The use of half-dose verteporfin photodynamic therapy in subjects with polypoidal choroidal vasculopathy was noninferior to when standard dose was used. Subgroup analysis showed that half dose was superior when certain baseline visual acuity and indocyanine green angiogram features were met. This offers an option for individualized regimen.